बसन्त के रंग - Ramesh Gupta (Aadivasi Lok Kala evm Boli Vikas Academy Madhya Pradesh Sanskriti Parishad, 2001)
Aiming to encourage researchers to attend and engage with folk cultures, the book identifies and outline approaches to the study of folk culture in the tribal regions of Madhya Pradesh.
Basant Ke Rang
Keywords: Folk Culture; Hindi